2016
DOI: 10.1186/s40792-016-0207-9
|View full text |Cite
|
Sign up to set email alerts
|

Chylous ascites associated with intestinal obstruction from volvulus due to Petersen’s hernia: report of a case

Abstract: BackgroundChylous ascites is an uncommon finding which is usually associated with recent abdominal/oncologic or retroperitoneal surgery. It is not usually seen in cases of acute obstruction.Case presentationA patient who had previously undergone a laparoscopy-assisted distal gastrectomy with Roux-en-Y reconstruction for early gastric cancer presented with acute abdominal pain and epigastric fullness. Computed tomography suggested small bowel obstruction due to volvulus. We were able to reduce the volvulus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…identified eight cases of CA associated with a SBO, all who underwent surgical intervention. All cases demonstrated bowel viability without the need for an enterectomy during surgery supporting the hypothesis that CA is an indicator of intestinal viability [ 8–11 ]. Clinical presentation includes abdominal distension with or without pain, nausea, anorexia, dyspnoea and oedema [ 1 , 2 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…identified eight cases of CA associated with a SBO, all who underwent surgical intervention. All cases demonstrated bowel viability without the need for an enterectomy during surgery supporting the hypothesis that CA is an indicator of intestinal viability [ 8–11 ]. Clinical presentation includes abdominal distension with or without pain, nausea, anorexia, dyspnoea and oedema [ 1 , 2 , 4 , 5 ].…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, both cases reported intestinal viability intra-operatively with no resection required. Furthermore, both studies hypothesized that CA associated with SBO may be an indication of intestinal viability, as veins and lymphatics operate at a lower pressure system and are the first to be occluded during a bowel obstruction, while arterial supply is required for lymphatic production and CA accumulation [ 8 , 9 ]. In addition, Akama et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, coexistence of chylous ascites and intestinal obstruction is rare, with only few case reports are published to date [2]. Among such studies, Akama et al [2] reported that chylous ascites indicates intestinal viability because when the literature was reviewed, it was observed that intestinal resection was not required when chylous ascites was found intraoperatively. The indication of intestinal viability by chylous ascites can be explained hypothetically as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Chylous ascites (milky ascites) is defined as an intraperitoneal accumulation of lymphatic fluid rich in triglycerides derived from the intraabdominal lymphatic system [1]. While the frequent causes of chylous ascites are due to the abdominal malignancy and traumatic (including surgical) damage to the lymphatic system, it is occasionally observed during surgery for intestinal obstruction, mainly small intestinal volvulus [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a dearth of published literature regarding chylous ascites, consisting only of case reports [5,[8][9][10][11][12]. We therefore aimed to characterize the frequency, associated conditions, and postoperative outcomes of chylous ascites in general surgery patients.…”
Section: Introductionmentioning
confidence: 99%